PEMBELAJARAN MELALUI BERMAIN BERBASIS KECERDASAN JAMAK PADA ANAK USIA DINI - Budiartati, Emmy (Universitas Negeri Semarang, 2007)
Play is a joyful activity and an inherent need for children so that children maylearn many skills in pleasure without any pressure. Trough play, children will be wellprepared for their environment and be ready on their next educational levels.Children’s intelligence is not only determined by a single score based on anintelligence test which measures the verbal, linguistic, and logical mathematicalcompetence. Children also have an intelligence which is called multiple intelligences.People have more or less 8 intelligences, which are verbal linguistic, logicmathematic, visual spatial, kinesthetic, music, interpersonal, intrapersonal, andnaturalistic. The multiple intelligences should be well understood by teachers, parents,and other educators. They should not develop only verbal, linguistic, and logicalmathematical intelligences. Developing multiple intelligences during early childhoodcan be conducted through a joyful play. Multiple intelligences apply in several steps,such as instruction plan, development of instruction strategies, and development ofinstruction evaluation.Kata kunci: pembelajaran melalui bermain, kecerdasan jamak, anak usia dini